2017
DOI: 10.1787/302b12bb-en
|View full text |Cite
|
Sign up to set email alerts
|

Business models for sustainable research data repositories

Abstract: This document, as well as any data and any map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Moreover, considering the socio-economic benefits of making research data open, a significant move towards open data access calls for trained manpower who can collect, store, manage, reuse and make research data openly accessible in academic and research institutions. It is anticipated that data specialists in large companies in the United Kingdom would increase at a growth rate of 243 % in five years 34 . Several Information Schools around the world have started short term courses in data management to train students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the socio-economic benefits of making research data open, a significant move towards open data access calls for trained manpower who can collect, store, manage, reuse and make research data openly accessible in academic and research institutions. It is anticipated that data specialists in large companies in the United Kingdom would increase at a growth rate of 243 % in five years 34 . Several Information Schools around the world have started short term courses in data management to train students.…”
Section: Discussionmentioning
confidence: 99%
“…The report of a study on the sustainability of digital repositories that was conducted by the Organization for Economic Co-operation and Development (OECD) concluded that "Research data repositories are an essential part of the infrastructure for open science…" [and that it] "is important to ensure the sustainability of research data repositories" 17 . The importance of the sustainability of research data infrastructure has been identified in studies describing the needs of archaeologists 9,18 .…”
Section: Impact Of the Trust Principlesmentioning
confidence: 99%
“…KB national Library of the netherlands, the Hague, the netherlands 16. University Libraries, columbia University, new York, USA 17. German climate computing center (DKRZ), Hamburg, Germany 18.…”
mentioning
confidence: 99%
“…The Organisation for Economic Co-operation and Development (OECD) has explored the income streams, costs, value propositions, and business models for 48 research data repositories. This survey is summarized in a report from 2017, including a set of recommendations on how to develop sustainable business models for repositories (OECD, 2017a). The authors of the report identify the following broad categories of business models being employed by research data repositories (OECD, 2017a, pp.…”
Section: B) Funding Should Be Tied To Sustainable Business Modelsmentioning
confidence: 99%